PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN VOLUNTARY DISCLOUSURE TERHADAP EARNING RESPONSE COEFFICIENT (ERC) - Herdirinandasari, Sherla Sherlia; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to examine the influence of firm size, profitability and voluntary disclosure to the earning response coefficient by taking the population of this research i.e. manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2014. The research samples have been selected by using purposive sampling technique; so that 47 companies (141 firm years) which have meet the criteria have been selected as samples. The data analysis technique has been done by using multiple regressions and hypothesis test by using SPSS 21st version. Based on the result of multiple regressions analysis with 5% significance level, therefore the result of this research shows that: (1) firm size has an influence to the earning response coefficient with the regressions value shows positive and unidirectional correlation, so that the first hypothesis is accepted; (2) Profitability has an influence to the earning response coefficient and shows positive and unidirectional correlation, so that second hypothesis is accepted; (3) Voluntary disclosure has an influence to the earning response coefficient and the regressions value shows positive and unidirectional correlation, so that the third hypothesis is accepted.Keywords: Firm Size, Profitability, Voluntary Disclosure, Earning Response Coefficient.